2021
DOI: 10.3390/ma14195575
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Service Environmental Parameters on Electrochemical Corrosion Behavior of L80 Casing Steel

Abstract: The corrosion behavior of L80 casing steel was studied in a simulating annulus environment using the electrochemical measurement method, immersion test, and tensile test under a high-temperature and high-pressure H2S/CO2 environment. The partial pressure of CO2 (PCO2), the partial pressure of H2S (PH2S), water content, and preloading stress remarkably affected the corrosion behavior of L80 steel. The influence of PCO2 on stress corrosion cracking (SCC) susceptibility has an inflection point of approximately 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“… 85 Sun et al. 86 also found that the corrosion potential of L80 steel shifted positively with the increase of P CO2 . The influence of P CO2 on corrosion potential and current is partly attributed to the pH change of CO 2 solution in corrosive medium.…”
Section: Influencing Factors On Carbon Dioxide Corrosionmentioning
confidence: 90%
“… 85 Sun et al. 86 also found that the corrosion potential of L80 steel shifted positively with the increase of P CO2 . The influence of P CO2 on corrosion potential and current is partly attributed to the pH change of CO 2 solution in corrosive medium.…”
Section: Influencing Factors On Carbon Dioxide Corrosionmentioning
confidence: 90%